Correction: Conditional autoencoder asset pricing models for the Korean stock market - Kim, Eunchong; Cho, Taehee; Koo, Bonha; Kang, Hyoung-Goo (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0281783.].